PERSEPSI PEMBERI PELAYANAN KESEHATAN TINGKAT I TERHADAP PROGRAM ASURANSI KESEHATAN/JPKM PERCEPTION OF PRIMARY HEALTH SERVICE PROVIDER TOWARD HEALTH INSURANCE PROGRAM) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Background: Health insurance is one of solutions to solve problem of health service cost increasing in Indonesia nowadays. One of the challenges that should be faced in implementing this program is readiness and ability of health service provider in controlling health quality and health cost. Aim: To know the perception of primary health service provider toward the relationship between health insurance organization and health care provider, payment system, work scope and expectation of health service provider in health insurance program Method: This research was using cross sectional design and the data was taken with quantitative and qualitative method. The subject of this research was 80 health care providers that consist of 50 doctors from 25 Primary Health Care who was chosen with cluster random sampling method and 30 family doctors in Yogyakarta Special Province. Variable being observed was: management health insurance organization that related with health care provider, payment system, work scope of health service provider. Instrument being used was questioner and interview guidance. Result: Perception of health care providers toward their relationship with health service institution was bad. This was because the health insurance organization rarely held meeting with the health service provider in order to discuss problem of health service and participation. Some of the respondents (27%) felt that this capitation payment system disadvantaged the health service provider and unfair. Indeed, this is considered as the main factor that influences the satisfaction of health care provider. Most of the respondents had good perception toward comprehensive care in the health insurance program (62,5%) although this job considered as routine activity and was not challenging. Conclusion: Generally, health care providers in the Primary Health Care had good perception toward health insurance program although this program still considered as a burden for them because of capitation system that was considered as insufficient. In addition, there was perception difference between Primary Health Care doctor and family doctor (private) toward collaboration contract and comprehensive care. Keywords: insurance â provider relationship, payment system, comprehensive care, health insurance